Analisis Pendapatan dan Kelayakan Usahatani Seledri (Apium Graveolens L.) di Desa Jati Bali Kecamatan Ranomeeto Barat Kabupaten Konawe Selatan - Sari, Yuni Kartika; Geo, La Ode; Gafaruddin, Abdul (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This study aims to determine the amount of celery farm income and to determine the feasibility of celery contained farm in the village of Jati Bali Subdistrict of Ranomeeto Barat District of Konawe Selatan. This research was conducted in January 2017 until Maret 2017. Act of determining sample in did with census method, the number population 25 of celery farmers. Data processed by use of income analysis and feasibility analysis. The results showed that income of celery which is Rp 132.401.484 with average income which is Rp 5.296.059 in one growing season. Feasibility level celery farm shows R/C Ratio of 3,16. This means that R/C Ratio> 1, farming profitable (or receiving additional benefits greater than the additional cost).